Cara merintis dan memulai start-up bisnis di usia remaja di Kota Sampang - Aini, Laily Nur; Khirdany, Elvin Nury; Qomariyah, Nurul; Shoffi, Robius (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Starting an entrepreneur must be considered, especially for teenagers in the industrial era 4.0. At Darus Syahid High School, Sampang, the cultivation of entrepreneurship is still not optimal; there are no entrepreneurship subjects in the learning process. This service aims to increase insight and motivate Darus Syahid Sampang High School students about starting entrepreneurship and to make it easier for students to carry out low-fund-based businesses that are effective and efficient for the needs of teenagers and even adults who want to start a business. The methods used in this community service are surveys, lectures, and discussions. This socialization will likely motivate teenage students to start entrepreneurship. This community service benefits both partners and participants (students), namely, increasing knowledge about entrepreneurship, success factors in entrepreneurship, and starting and maintaining a business. After attending the training, participants expressed high satisfaction with the implementation.